Mise en œuvre de politiques municipales jeunesse et sports : quand les « jeunes-vieux » dans les quartiers deviennent une catégorie d’action publique officieuse et émergente - Coralie Lessard (Sociétés et Jeunesses en Difficulté, 2021)
In a societal context made up of vigilant government public policies about the risk of terrorism, this article questions about methods of municipal public action towards the “young” and the “not so young” in disadvantaged neighborhoods, like particular target groups. The emergence and treatment of the informal category of “young old people” are analyzing within the specific framework of municipal Youth and Sports institutions in the districts. And that, even though the traditional missions of these institutions are no longer necessarily designed to take care of them. The issue spread both to the redefinition of the boundaries of the action of these institutions and to the modalities for supervising youths perceived as undesirable. This article questions about the relevance of the measures undertaken by socio-sports policies. Forms of social control of “young old people” which are disturbing and frightening in disadvantaged neighborhoods are made possible, because the approach is not incompatible with the immediate expectations of this public in terms of leisure; in this context, the effectiveness of the socio-sports policies studied is questioned.